Psychological and behavioural difficulties following severe TBI in adolescence: a comparison with a sample of peers with brain lesions of other origin and with a control group. (3rd July 2018) - Pastore, Valentina; Galbiati, Susanna; Recla, Monica; Colombo, Katia; Beretta, Elena; Strazzer, Sandra
ABSTRACT: Objective : To describe behavioural and adjustment problems in a group of 57 adolescents with severe traumatic brain injury (TBI) and compare them with a clinical group of peers with brain lesions of other origin ( N  = 33) and a control group of healthy adolescents ( N  = 48). Methods : All subjects received an age-appropriate assessment, including the child behaviour checklist (CBCL) 4/18, the strengths and difficulties questionnaire (SDQ) and the vineland adaptive behaviour scales (VABS). Results : Compared with healthy peers, adolescents with TBI presented with more marked behavioural problems on most CBCL scales (Internalization and Externalization domains were both affected) and on the SDQ Hyperactivity and Peer problems scales. They also showed a more impaired functioning in most VABS domains. Compared with adolescents with brain lesions of other aetiology, patients with TBI showed more conduct problems on the SDQ scale, but no significant differences were found on the CBCL scales. Regarding the VABS, patients with other lesions presented with the worst outcome in the Motor and Daily Living Skills domains. Conclusions : Adolescents with TBI are exposed at a very high risk to develop behavioural and psychological disturbances with the potential to severely affect their social re-entry. Further knowledge is needed to plan early and well-timed interventions.